Fenomena Korean Wave dan Fanatisme Penggemar Dalam Bermedia Sosial Studi Kelompok Fandom di Kota Pontianak: Fenomena Korean Wave dan Fanatisme Penggemar Dalam Bermedia Sosial Studi Kelompok Fandom di Kota Pontianak - Viza Juliansyah; Desca Thea Purnama; Chyntia Maharani (Jurnal Sosiologi Nusantara, 2024)
This research discusses the phenomenon of the Korean Wave and fanaticism communities (fandom) in social media to bring the influence and impact of the Korean Wave phenomenon in Indonesia. This research aimed (1) to describe how the Korean Wave phenomenon can create fanatical fandom in social media; (2) to outline the forms and patterns of fanatical fandom towards K-Pop; (3) to identify the factors that influence the behavior and the consequences of such fanatical behavior. The research method used was descriptive with a qualitative approach. The subjects of this study were K-Pop fans, both those associated with the fandom and those who are not. The participants were gathered using the snowball technique, while data collection used observation, interviews, and documentation. The results showed that introducing foreign cultures, including the Korean Wave phenomenon, can lead to fanatical behavior among fans. This behavior is characterized by intentionally building emotional bonds to strengthen the connection between fans and idols. In addition, the shared identity as fans creates a strong solidarity among themselves. Excessive solidarity can indirectly lead to negative energy that harms others and can lead to conflicts. Furthermore, social media, marketing strategies, and the attractiveness of K-Pop idols also shape fanatical behavior.